Fracture Resistance of New Fiber Post System (Rebilda GT) - Emad Farhan Alkhalidi (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background and Aims: Evaluate and compare the fracture resistance of endodontically treated teeth restored with bundle glass fiber post and tapered glass fiber post, at 45 degree oblique load. Materials and Method: Thirty newly extracted single rooted mandibular first premolars were chosen, and after root canal preparation and obturation, post spaces were prepared. Then the samples were separated into three groups (n = 10) dependent on the type of restorative method used: group A restored with Rebilda fiber post [tapered glass fiber post], group B restored with Rebilda post GT post system (bundle glass fiber post), and group C restored with direct composite resin restoration without a post (control). Using a universal testing machine with speed of 0.5 mm/minute at 45 degree sloping load which was applied to the restored teeth, fracture resistance was recorded in Newton. Results: The results showed that the fracture resistance significantly affected by different post systems (p < 0.05). The bundle glass fiber post (rebilda Gt) showed highest fracture resistance than the other groups. Conclusion: Rebilda GT post (bundle glass fiber system) showed higher fracture resistance than the Rebilda fiber post (tapered glass fiber post) and control group respectively